The time‐resolved and extreme conditions XAS (TEXAS) facility at the European Synchrotron Radiation Facility: the general‐purpose EXAFS bending‐magnet beamline BM23. (19th October 2015) - Mathon, O.; Beteva, A.; Borrel, J.; Bugnazet, D.; Gatla, S.; Hino, R.; Kantor, I.; Mairs, T.; Munoz, M.; Pasternak, S.; Perrin, F.; Pascarelli, S.
Abstract : BM23 is the general‐purpose EXAFS bending‐magnet beamline at the ESRF, replacing the former BM29 beamline in the framework of the ESRF upgrade. Its mission is to serve the whole XAS user community by providing access to a basic service in addition to the many specialized instruments available at the ESRF. BM23 offers high signal‐to‐noise ratio EXAFS in a large energy range (5–75 keV), continuous energy scanning for quick‐EXAFS on the second timescale and a micro‐XAS station delivering a spot size of 4 µm × 4 µm FWHM. It is a user‐friendly facility featuring a high degree of automation, online EXAFS data reduction and a flexible sample environment.